Former Central European Free Trade Agreement countries' agri-food trade specialisation - Stefan Bojnec; Imre Ferto (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2009)
The paper evaluates agri-food trade competitiveness and specialisation patterns of the former Central European Free Trade Agreement (CEFTA-7) countries compared with the European Union (EU-15) from 1995-2007. Agri-food trade specialisation stability and duration are investigated by main agri-food product groups according to the degree of product processing and dynamics in the demand growth exhibited by the EU-15 market. Except for Poland and Hungary, the former CEFTA-7 countries face a trade deficit in agri-food products with the EU-15 markets. The former CEFTA-7 agri-food exports to EU-15 markets are specialised towards higher-value, processed, consumer-ready food as a result of agri-food sector restructuring and integration to more competitive EU markets. The former CEFTA-7 agri-food export specialisation towards the EU-15 markets' most demanded products is also revealed. The results confirm that EU integration increases size of trade, stability, and the duration of former CEFTA-7 agri-food trade products on EU-15 markets.
Keywords: 330; Agrarproduktion; Agraraußenhandel; Internationaler Wettbewerb; Freihandelsabkommen; CEFTA-Staaten